A Guide to Public Engagement for Entomological Collections and Natural History Museums in the Age of Social Media. (6th September 2017) - Lessard, Bryan D.; Whiffin, Ashleigh L.; Wild, Andrea L.
Abstract: Social media has revolutionized the way research and museum collections communicate with the general public by disseminating knowledge and information in real time. Currently there are limited studies examining the use of social media by museums and entomological collections to engage the general public online. Social media has the power to promote museum and collection events, research, and staff, as well as raise awareness of entomological collections and demonstrate their relevance to the public, industry, policy makers, and potential students of entomology. Here we introduce SCOPE, a new framework for promoting museums and entomological collections using social media. The SCOPE framework streamlines strategy development, content choice, refinement of online engagement, choice of social media platform, and evaluation of social media campaigns using altmetrics. Case studies from the Australian National Insect Collection, CSIRO, and National Museums Scotland following the SCOPE framework are provided so that other museums, entomological collections, staff, and students can replicate it to develop and maintain their own social media presence.